Techno-economic evaluation of broadband access alternatives for ip services - Robert Jankovsky; Radoslav Odrobinak (Communications - Scientific letters of the University of Zilina, 2004)
This paper deals with a techno - economic evaluation of broadband upgrade strategy for IP services. This scenario is focused on the FTTcab/VDSL architecture with ATM versus Ethernet approaches. Target market is residential customers and small business customers in urban and dense urban areas. Installed First Cost (IFC) and Net present Value (NPV) as main techno - economic results are discussed regarding common assumptions. The results show that the choice of technology (Ethernet or ATM) has almost no effect on the cost level and profitability of the cases.